Gaya Bahasa Puisi Pada Buku Kumpulan Puisi Buku Latihan Tidur Karya â€œJoko Pinurboâ€ - Hermawan, Agus (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2020)
Abstractâ€” Literary works are works of art created by the author, through the writing of literary works that he makes, writers or authors use their imagination and are expressed through words, forming language as a form of his imagination. For this reason, understanding of literary works cannot only be studied for its intrinsic elements, but also for its extrinsic elements. The author's Sleeping Exercise Book for Poetry Collection â€œJoko Pinurboâ€ presents poetry titles that are very interesting and easy to remember by literary lovers and audiences. Based on this, the researcher is interested and wants to prove and describe the uniqueness and attractiveness of the poetry titles of "Joko Pinurbo" Poetry Sleeping Exercise Book, especially in the style of language used in the work.Â Keywordsâ€”: Literary works; Poutry; language style.